The relationship between norms and hegemony : exploring international drug prohibition over the last 100 years - Sweenie, Kaitlin Elizabeth (Department of Political Studies, 2016)
It is just over fifty years since the United Nations adopted the Single Convention on Narcotic Drugs (1961), explicitly proscribing the manufacturing of, trade in, and use of narcotics for anything but scientific and medicinal purposes. Today, the 1961 agreement, alongside the similarly-focused 1971 and 1988 UN Conventions remain the bases of the international drug control regime despite the continuously high rates of drug use, trade, and production that remain worldwide. Taking due cognizance of these inconsistencies, the present study seeks to examine how the system of international drug control developed over the past century and, through this, why it is that prohibition continues to be the international community's primary response to the 'drug issue'. Methodologically, the study applies two distinct analytical frameworks. The first framework applied - Kathryn Sikkink and Martha Finnemore's constructivist norm life-cycle model - systematically traces the evolution of the norm of prohibition over time and helps identify the main causal mechanisms at work in each stage of the norm's life. While the model is successful in regards to these aforementioned aspects, however, the research also shows the model does not adequately examine the role of power in international norm dynamics. The model, more specifically, does not discuss how existing power relations can help sustain a norm's livelihood long past its (perceived) effectiveness. Additionally, it is also shown through this application that prohibition did not develop in the exact manner the model suggests it would, but became institutionalised only in its final, internalisation phase instead of its emergent phase. In this manner, the second theoretical framework - that of Robert Cox's critical theory - is consequently introduced to address the life cycle's limitations. By applying Cox's ideas on hegemony - herein understood as a fit between material power, ideas, and institutions - the study demonstrates how the hegemony of (primarily) the United States (US) has always and continues to play a leading role in supporting the norm of international drug prohibition today. The study concludes with some final notes about further research and the possibilities for change.